Pengembangan Pembelajaran PAI Melalui Inovasi Bahan Ajar Multimedia di Kelas XI SMK Al Hidayah - Dinda Syifa Dahlia; Indriani Samba Purwanti; Achmad Abdurrouf; Ahmad Zuhair Syafiq; Afif Maulana (PT. Pusmedia Group Indonesia, 2024)
This study aims to evaluate the use of multimedia teaching materials in learning in class XI of SMK Al Hidayah, focusing on aspects of success, obstacles, and implementation implications. Education in the modern era demands innovation in learning methods, and the use of technology, such as multimedia teaching materials, is considered as one of the approaches that can improve the quality of learning. This research is conducted using an evaluative approach that involves analyzing the effectiveness of using multimedia teaching materials, identifying the barriers that may arise, and exploring the implications of implementing the technology on the learning process. The research methodology involved quantitative and qualitative data collection, including surveys, observations, and interviews with teachers and students in grade XI. The results illustrate the success rate of using multimedia teaching materials, the obstacles faced, and the impact on the learning process. The conclusions of the study provide an in-depth insight into the effectiveness of technology in learning within SMK Al Hidayah. The implications of the findings are expected to provide a foundation for the development of better learning strategies in the future. By evaluating the use of multimedia teaching materials, this research contributes to further understanding of technology integration in the context of vocational secondary education. Keywords: Islamic Education Learning; Teaching Materials; Multimedia